1997
DOI: 10.1002/(sici)1097-4547(19970615)48:6<551::aid-jnr8>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DA11, a neuronal-injury-induced fatty acid binding protein, coincides with axon growth and neuronal differentiation during central nervous system development

Abstract: DA11 is the first fatty acid binding protein (FABP) for which gene expression has been shown to be upregulated following neuronal injury in the adult peripheral nervous system. To understand better the potential regulatory role(s) of this unique FABP in axonal growth and neuronal differentiation, we undertook a temporal and spatial study of DA11 gene expression in the developing rat central nervous system (CNS). Transient upregulation of DA11 mRNA and protein levels in CNS tissues were quantified by Northern b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 62 publications
3
29
0
4
Order By: Relevance
“…In mouse brain, H-FABP levels are detectable after fetal day 19 and increase until post-natal day 14, but become lower in the adult brain [221]. In contrast to H-FABP, the expression of B-FABP and E-FABP is dominant in the pre-natal and peri-natal mouse and rat brain [219,220]. E-FABP mRNA and protein are expressed at high levels during neurogenesis, neuronal migration and terminal differentiation of neurons [219,222].…”
Section: Expression Of Fabps and Their Role In Growth Differentiatiosupporting
confidence: 92%
See 2 more Smart Citations
“…In mouse brain, H-FABP levels are detectable after fetal day 19 and increase until post-natal day 14, but become lower in the adult brain [221]. In contrast to H-FABP, the expression of B-FABP and E-FABP is dominant in the pre-natal and peri-natal mouse and rat brain [219,220]. E-FABP mRNA and protein are expressed at high levels during neurogenesis, neuronal migration and terminal differentiation of neurons [219,222].…”
Section: Expression Of Fabps and Their Role In Growth Differentiatiosupporting
confidence: 92%
“…The brain contains three different types of FABP: H-FABP [47], B-FABP [217,218] and E-FABP [20,219]. The genes for these brain FABP types show a spatiotemporally differential expression in developing and mature brain [219,220]. The expression of H-FABP becomes evident in rat brain after birth, with a gradual increase, and is confined to the grey matter, suggesting that its mRNA is neuron specific [220].…”
Section: Expression Of Fabps and Their Role In Growth Differentiatiomentioning
confidence: 99%
See 1 more Smart Citation
“…However, its mRNA was later found to be expressed in various tissues including adipose tissue 5,8,9,[12][13][14][15][16][17][18][19][20][21][22][23] . Krieg et al 5) examined levels of C-FABP mRNA in mouse tissues, and found that the mRNA was most abundant in stratified epithelia of the epidermis and tongue.…”
Section: Discussionmentioning
confidence: 99%
“…1). Together with the uptake and delivery of fatty acids within the neurogenic niches, FABP are assigned to play crucial roles in the cell growth and differentiation (110,116,117) by regulating certain transcription factors. Targeted transcription factors are the members of the peroxisome proliferatoractivated receptor (PPAR) family, comprising of three isotypes -PPARα, PPARγ, and PPARδ/β (118,119), with PPARδ/β abundantly expressed in the CNS (120).…”
Section: Fabp In the Neurogenic Nichementioning
confidence: 99%